Therapeutically engineered induced neural stem cells are tumour-homing and inhibit progression of glioblastoma - Bagó, Juli R. (Nat Commun, 2016)
Transdifferentiation (TD) is a recent advancement in somatic cell reprogramming. The direct conversion of TD eliminates the pluripotent intermediate state to create cells that are ideal for personalized cell therapy. Here we provide evidence that TD-derived induced neural stem cells (iNSCs) are an efficacious therapeutic strategy for brain cancer. We find that iNSCs genetically engineered with optical reporters and tumouricidal gene products retain the capacity to differentiate and induced apoptosis in co-cultured human glioblastoma cells. Time-lapse imaging shows that iNSCs are tumouritropic, homing rapidly to co-cultured glioblastoma cells and migrating extensively to distant tumour foci in the murine brain. Multimodality imaging reveals that iNSC delivery of the anticancer molecule TRAIL decreases the growth of established solid and diffuse patient-derived orthotopic glioblastoma xenografts 230- and 20-fold, respectively, while significantly prolonging the median mouse survival. These findings establish a strategy for creating autologous cell-based therapies to treat patients with aggressive forms of brain cancer.